PENGARUH GAYA HIDUP, STRATEGI PROMOSI DAN PERSEPSI HARGA TERHADAP KEPUTUSAN PEMBELIAN PADA PENGGUNA SHOPEEFOOD DI KOTA DENPASAR - Mulyadi, Made; Putri Virgiantari, Ni Made; Nengah Wirsa, I; Gede Elvina Adi Saputri, Luh (Penerbit Lafadz Jaya, 2025)
This research investigates the influence of lifestyle, promotional strategies, and price perceptions on purchasing decisions of ShopeeFood users in Denpasar City. Focusing on the dynamics of the rapidly growing online food delivery market, this research analyzes the factors that influence consumer purchasing decisions. Statistical data from respondents shows that lifestyle, promotional strategies and price perceptions significantly influence user preferences for using the ShopeeFood platform. The findings show that convenience, attractive promotional tactics, and perceived affordable prices are key factors in motivating users to choose ShopeeFood as a food delivery platform. This research reinforces previous findings about the importance of these factors in influencing consumer purchasing behavior in the online food delivery service industry.